2015
DOI: 10.1111/pops.12258
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Appeal of Populist Right‐Wing Parties in Times of Economic Prosperity

Abstract: The assumption that populist right‐wing parties (PRWPs) thrive when the economy slows down is remarkably pervasive. What is often neglected is evidence showing PRWPs can thrive in times of economic prosperity. To examine this, we conducted an experiment in which participants were exposed to different appraisals of the future of the national economy and were subsequently asked to evaluate an anti‐immigration speech (Study 1). Results showed stronger anti‐immigrant sentiments when the national economy was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 35 publications
(44 reference statements)
10
139
3
2
Order By: Relevance
“…Explicit random assignment to wealth does not fully simulate inheriting or earning wealth. That being said, there is mounting evidence of a link between economic prosperity, instability, and the appeal of radical anti‐immigration parties and movements (Betz, ; Lubbers, Gijsberts, & Scheepers, ; Mols & Jetten, ). Our experimental findings chime well with the finding that populist right‐wing parties have done remarkably well in times of economic instability and among relatively wealthy groups of voters (see Mols & Jetten, forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…Explicit random assignment to wealth does not fully simulate inheriting or earning wealth. That being said, there is mounting evidence of a link between economic prosperity, instability, and the appeal of radical anti‐immigration parties and movements (Betz, ; Lubbers, Gijsberts, & Scheepers, ; Mols & Jetten, ). Our experimental findings chime well with the finding that populist right‐wing parties have done remarkably well in times of economic instability and among relatively wealthy groups of voters (see Mols & Jetten, forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that collective narcissism stimulates disruptive forms of protest (Górska & Bilewicz, 2017), which might at least partially explain why we often observe violent behaviors at populist rallies (Jacobs, 2016;Kellner, 2016). Such defensive responses might be especially likely when objectively privileged groups are led to believe they are relatively disadvantaged and threatened by minorities (Mols & Jetten, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, empirical research in Poland demonstrated that feelings of relative deprivation were indeed associated with support for Law and Justice (Winiewski, Jurczyszyn, Bilewicz, & Beneda, 2015). Furthermore, Mols & Jetten (2016) demonstrated that populist leaders can present situations of objective relative gratification (i.e., being relatively better off than others) under the guise of relative deprivation to manipulate the public. Such perceptions create feelings of injustice and resentment towards outgroups, including immigrants, who might be perceived as threatening the disadvantaged group's interests (e.g., Cramer, 2016;Doosje, Loseman, & van den Bos, 2013;Mols & Jetten, 2016).…”
mentioning
confidence: 99%
“…Innvandringsskepsis er for eksempel blitt framhevet som en viktig årsak til at det ble flertall for utmelding av EU i den britiske folkeavstemningen i juni 2016, eller at Trump vant det amerikanske presidentvalget i november. I Norge har Fremskrittspartiet foreløpig ikke hatt samme suksess som innvandringsskeptiske partier i flere andre europeiske land, der det politiske landskapet er i sterk endring (Mols & Jetten 2016). Men gjennom å sitte i regjering og ha ansvar for dette saksområdet, har partiet kunnet arbeide for at Norge skal «få en asylpolitikk som er blant de strengeste i Europa» (Sylvi Listhaug til NTB i november 2015).…”
Section: Innledningunclassified